The use of weightlifting pulling movements in sport - Introduction /snatch versus the clean - Stone, M.; Stone, Mike; Gattone, M.; Schilling, B.; Pierce, K.; Byrd, R.
The purpose of this discussion is to: first describe the proper technique used in the pulling portion of the snatch and clean, second examine the potential importance of these lifts for sport and third to examine the potential outcome of training in a similar manner as weightlifters.